3(4+-a)=2(6+a)

Simple and best practice solution for 3(4+-a)=2(6+a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4+-a)=2(6+a) equation:



3(4+-a)=2(6+a)
We move all terms to the left:
3(4+-a)-(2(6+a))=0
We add all the numbers together, and all the variables
3(-1a)-(2(a+6))=0
We multiply parentheses
-3a-(2(a+6))=0
We calculate terms in parentheses: -(2(a+6)), so:
2(a+6)
We multiply parentheses
2a+12
Back to the equation:
-(2a+12)
We get rid of parentheses
-3a-2a-12=0
We add all the numbers together, and all the variables
-5a-12=0
We move all terms containing a to the left, all other terms to the right
-5a=12
a=12/-5
a=-2+2/5

See similar equations:

| 5x+2x=58-9 | | 1/3(7x-1)=2x+3 | | 12x²+17x=5 | | 4x+3x+3=48 | | 9x+8x+4x-5=34 | | 12x²+18x=x+5 | | 6(m+5=18 | | x+2x-1+0.5x=51.50 | | m÷8-16=-52 | | 3x+48=5x+2 | | 2/3x=9/7 | | x+0.15x=97.75 | | 0=-7/3x+14 | | x2+3x-154=0 | | 5x+40=8x+37 | | 2n+4=145 | | 17^-x-7=4^-2x | | 6(5x+3)-7=101 | | 6x+42=8x+10 | | 26z=-29 | | -3x-15=-89 | | 8d2−8d−4=0 | | 9x+4x-2x-5=61 | | (1/3)(9c-36)=-9 | | 1100+7x=18000 | | 0.5(x+50)+0.9x=74 | | 2n-1/4=10 | | -34+5x=-64 | | 9u=2.5 | | 2.5t=9 | | 24.5=3v-2v | | 42=24+2a |

Equations solver categories